2019
DOI: 10.1002/1348-9585.12093
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of occupational noise-related hearing impairment among dental health personnel

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 32 publications
1
20
0
8
Order By: Relevance
“…In our study, the profession of dentist does not seem to induce a higher incidence of NIHL than controls. Our data are in line with previous reports [15,[26][27][28]31], while others reported contrary results [11,13,14,[23][24][25]46,47]. Since both older cohorts had been working for more than 20 years on average and show similar incidence of HL, our study cannot confirm that duration of exposure significantly affects hearing in dentistry, as was reported by Gurbuz, who found a significant correlation between the total working duration (years × days × hours) and the level of HL at all frequencies [11].…”
Section: Hearing Losssupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, the profession of dentist does not seem to induce a higher incidence of NIHL than controls. Our data are in line with previous reports [15,[26][27][28]31], while others reported contrary results [11,13,14,[23][24][25]46,47]. Since both older cohorts had been working for more than 20 years on average and show similar incidence of HL, our study cannot confirm that duration of exposure significantly affects hearing in dentistry, as was reported by Gurbuz, who found a significant correlation between the total working duration (years × days × hours) and the level of HL at all frequencies [11].…”
Section: Hearing Losssupporting
confidence: 93%
“…While the exposure levels of contemporary dental equipment may have become less hazardous in time, occupational HL remains a matter of debate. Some studies have reported poorer hearing thresholds for dental professionals compared to controls [11,13,14,[23][24][25], while others report similar hearing thresholds [15,[26][27][28]. Audiometric patterns generally reflect a mild hearing impairment between 2 and 6 kHz, but by no means with all dental professionals (e.g., [14]).…”
Section: Introductionmentioning
confidence: 99%
“…Many dental equipment generate sounds and significantly increase the noise levels in the working environment for DCPs [ 58 , 59 ], which may contribute to hearing loss in dental professionals [ 60 , 61 ]. The high-volume evacuation commonly used during dental procedures raised the noise level to 77 dB [ 35 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, hearing loss was more among dental professionals as compared to dental assistants and technicians. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%